(untitled) (Revista de Artes Marciales Asiáticas, 2017)
The present work investigated the use of wushu at school by Physical Education teachers (PEF) as a tool for the motor, cognitive and socioaffective development, and compared practitioners and non-practitioners in concept, understanding and application of wushu resignified practices in Elementary School grades I and II in São Paulo, Brazil. For this purpose, 40 PEFs were assigned to one of two groups, wushu Practitioners (PW, n=27) or Non wushu Practitioners (NPW, n=13). All participants answered a questionnaire composed of 11 objective questions about the wushu practice by schoolchildren, with answers ranging on four levels ("does not attend", "partially", "fully" and "exceeds"). The Mann Whitney test was used to compare the responses, p<0.05. Results showed differences between groups, in which PW considered wushu a valid content to teach aspects related to martial arts for schoolchildren, while NPW believed to be inefficient. Both groups identified wushu as an activity that meets and exceeds the needs of motor, cognitive and socioaffective development in schoolchildren. On the other hand, about 30% of NPWs indicated that wushu is difficult to use in schoolchildren, and 40% of NPWs reported that wushu practices during initial teacher training were only partially or not sufficiently taught. These results suggest the possibility of a relationship between the teachers’ experience and the promotion of certain practices, depending the teaching of martial arts on the teachers’ practical experience.